Gender and depression: dual pathways influencing adolescents' physical activity and psychological wellbeing - Bai, Dan; Wu, Mingdong; Pang, Ying; Liu, Xiaoming (Frontiers in Public Health, 2025)
ObjectivesThis study investigates the influence of gender and depression on physical activity (PA) and psychological wellbeing among adolescents in Shanghai.MethodsA purposive offline survey conducted from June to December 2023 collected data from 416 participants (216 boys, 200 girls). This study employed SPSS software version 29 to conduct descriptive statistics and multivariate analysis of variance (MANOVA).ResultsThe findings revealed a significant gender difference in moderate-to-vigorous physical activity (MVPA), with boys reporting higher levels than girls (η2 = 0.05). However, gender did not significantly affect psychological variables, including academic self-efficacy (ASE), mindfulness (MD), emotional intelligence (EI), self-esteem (SE), and social support (SS). Depression levels had a significant impact on all psychological variables, with students experiencing low depression scoring higher on ASE, MD, EI, SE, and SS compared to those with high depression (η2 = 0.11–0.25). Conversely, depression levels did not significantly influence MVPA.ConclusionsThese results emphasized the critical role of addressing depression to improve adolescents' psychological wellbeing while highlighting the need for gender-specific interventions to encourage physical activity (PA).